تطبيق استراتيجية التدريس التبادلي في ترقية نشاط الطلاب بالمدرسة المتوسطة الإسلامية بجاكرتا - Hannum, Aisyah; Nawawi, Mukhshon; Matin, Iman (Department of Arabic Education - Faculty of Educational Sciences, 2024)
This research aims to reveal the application of reciprocal teaching and its impact on improving student activity in class VIII (1) at MTs. Annajah Jakarta. This research is quantitative, using experimental research with a one-group pretest-posttest design. The researcher used data collection techniques through direct observation, interviews, and questionnaires. In the data analysis, the researcher calculated the average, questionnaire calculations, and a t-test (Paired Sample T-test) for normality testing using the IBM SPSS statistics. The research result is (1) the average observation in post test is 82.22, which is higher than the average pre-observed 42.33; (2) the value is 7.243, and a significant level at 5% is 2, 039 so the result is higher than tt. So the research hypothesis shows that Ha is accepted and Ho is rejected. Therefore, the researcher concluded that applying the reciprocal teaching strategy increased student activity.